Analysis Of The Relationship Of Rare Earth Elements To Magnetic Minerals In Pumice In The Southern Tip Of Lampung Province - Rifqa Hayati; Hamdi Hamdi; Letmi Dwiridal; Harman Amir (Department of Physics, Universitas Negeri Padang, 2023)
In advanced clean energy technologies, rare earth elements (REEs) are an important component. The position of rare earth elements in the future is increasingly strategic so it is necessary to strive to be developed sustainably. At the southern tip of Lampung province, rare earth elements are not yet known. The aims of this study were to analyze the magnetic susceptibility value, composition and percentage of rare earth elements, and the relationship of rare earth elements with magnetic mineral concentrations in pumice at the southern tip of Lampung Province. The method employed is rock magnetic method with Bartington Magnetic Susceptibility Meter Type B and X-Ray Fluorescence. Pumice in the southern region of Lampung Province has diverse magnetic susceptibility values, pumice from Bandar Lampung City has the highest magnetic susceptibility value, while the lowest is in South Lampung Regency. This pumice has antiferromagnetic and ferrimagnetic magnetic properties, and was found to have almost no superparamagnetic grains and also found a mixture of superparamagnetic and coarse grains. The composition of rare earth elements contained in pumice at the southern tip of Lampung Province obtained 3 rare earth elements, samples from Bandar Lampung City contained europium, cerium, and yttrium elements and samples from South Lampung Regency contained europium and yttrium elements. Rare earth elements and magnetic mineral concentration have a relationship, the obtained values decrease with increasing percentage of rare earth elements.